2001
DOI: 10.1080/713602888
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid peroxide levels and erythrocyte glutathione peroxidase and superoxide dismutase activity in premenopausal and postmenopausal women

Abstract: Free radical reactions are involved in processes connected with aging. Estradiol acts as antioxidant and free radical scavenger, but the mechanism of this action remains unknown. Estradiol has a hydroxyphenolic structure and may donate hydrogen atoms to lipid peroxyradicals to terminate chain reactions. There are a few reports concerning the influence of estradiol on natural antioxidant enzyme activity, such as superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT). The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 0 publications
7
43
0
Order By: Relevance
“…28 PMW have been shown to have reduced glutathione peroxidase activity, but not superoxide dismutase (SOD). 29 In fact, Gurdol and colleagues 30 found that Cu,Zn-SOD was elevated in aging PMW, but glutathione peroxidase activity was reduced. Therefore, it is possible that PMRs, but not male SHR, may have adequate SOD activity but have a deficiency in catalase or glutathione peroxidase that makes it difficult to remove H 2 O 2 and the radicals (eg, hydroxyl) produced by its metabolism.…”
Section: Characteristics Of Aging In Female Shrmentioning
confidence: 99%
“…28 PMW have been shown to have reduced glutathione peroxidase activity, but not superoxide dismutase (SOD). 29 In fact, Gurdol and colleagues 30 found that Cu,Zn-SOD was elevated in aging PMW, but glutathione peroxidase activity was reduced. Therefore, it is possible that PMRs, but not male SHR, may have adequate SOD activity but have a deficiency in catalase or glutathione peroxidase that makes it difficult to remove H 2 O 2 and the radicals (eg, hydroxyl) produced by its metabolism.…”
Section: Characteristics Of Aging In Female Shrmentioning
confidence: 99%
“…(b) There is a long-term protective effect of pregnancy in breast cancer, and pregnant women exhibit significantly higher lipid peroxidation levels than nonpregnant women (52). (c) Breast cancer risk is reduced by oophorectomy and menopause, conditions both associated with significant increases in lipid peroxidation (53)(54)(55). (d) Hormone replacement therapy (combined estrogen plus progestin) increases breast cancer risk and significantly decreases lipid peroxidation in postmenopausal women (56)(57)(58).…”
Section: Epidemiology Of Breast Cancer: Role Of Lipid Peroxidationmentioning
confidence: 99%
“…Similarly, several studies compared serum/plasma lipid peroxide levels of normal premenopausal and postmenopausal women and have found a significant increase in serum/ plasma lipid peroxides after natural menopause (55,136,137).…”
Section: Epidemiology Of Breast Cancer: Role Of Lipid Peroxidationmentioning
confidence: 99%
“…36 Likewise, Se levels have been shown to vary according to estrogen status over the female lifespan, 37 with levels of estradiol and GPX activity significantly higher in premenopausal than postmenopausal women. 38 This link between estrogen and Se metabolism has been further substantiated by recent evidence of a direct correlation between estradiol, plasma Se and plasma and erythrocyte GPX activity, 39 possibly revealing why the beneficial effect of Se on HCC risk might be greater in women, especially premenopausal women. Although menopausal status was not ascertained, the majority of women studied were likely pre-or perimenopausal at baseline, given their age distribution.…”
Section: Overallmentioning
confidence: 85%